Vaccines for prostate cancer : a new era? - Mulia, Julius I (Faculty of Medicine, Trisakti University, 2009)
Prostate adenocarcinoma is the most prevalent type of noncutaneous cancer in the Western world, with an estimated 218,890 new cases and 27,050 deaths in the United States in 2007. Currently prostate cancer is detected by measurement of prostate-specific antigen (PSA), a serine protease synthesized by the prostatic epithelium. PSA is an organ-specific and tumor-associated antigen (TAA) but it is not tumor-specific.(1) Partly because of increased cancer screening with PSA, prostatic cancer may now be diagnosed when it is still localized. Localized tumors of the prostate are generally treated with radical prostatectomy, external-beam radiation therapy (EBRT), brachytherapy, or watchful waiting. Unfortunately, up to 30%-40% of patients fail local therapy. The standard treatment of recurrent or metastatic disease is androgen-deprivation therapy (ADT), but this is only a temporary measure as in the majority of cases the cancer ultimately becomes hormone refractory, the condition being termed androgen-independent prostate cancer (AIPC) or hormone refractory prostate cancer (HRPC), which then progresses rapidly. The only available nonpalliative therapy for androgen-independent prostate cancer is docetaxel in combination with prednisone. However, ADT given prior to the onset of clinical symptoms results in rising PSA levels with castrate levels of testosterone, often with a relatively low tumor burden. This systemic treatment earlier in the disease course combined with effective palliative chemotherapy is implicated in the improvement in median survival time of patients with AIPC from an average of about 12 months to about 17-18 months.